Gasification of Coffee Parchment as Potential Method for Coffee Agro-Industry Waste Utilization - Zahra Fona; Adi Setiawan; Irvan Irvan; Rondang Tambun; Fatimah Fatimah; Muhammad Hadiansyah; Zein Ramadani (Jurnal Rekayasa Kimia & Lingkungan)
Coffee parchment is a lignocellulosic waste material which has a potential to transform into synthesis gas. This research aims to study the feasibility of coffee parchment conversion under downdraft gasification with ‘auto-heating’ supply method. The temperature profile in each zone of the reactor was investigated as the effect of different equivalence ratio (ER) as well as the producer gas characteristics such as ignition time, flame duration, colour and temperature, carbon conversion and producer gas composition. Initially, coffee parchment collected from dehulling process was sun-dried three to four days. The gasification was ignited by firing ca. 300 g of wood charcoal inside the reactor before the coffee parchment loaded, then the reactor was tighly closed. Once the combustible gas was produced, the gasification time was measured. The result shows that the highest operational temperature inside the reactor was 715.66 °C within the combustion zone. The biomass conversion tends to increase by the increasing of ER, but the producer gas might dilute by more carbon dioxide production, and nitrogen input into the producer gas which indicated by the flame duration, colour, and temperature. Introducing an ER of 0.3 into the gasification reactor has provided adequate amount of oxygen to convert the coffee parchment into producer gas. This investigation suggests that coffee parchment is feasible to be converted into syngas. However, providing an advance process integrated to cleaning system would be required in the future to obtain a fuel grade syngas.